Impact of dopamine-related genetic variants on physical activity in old age - a cohort study - Ing-Mari Dohrn; Goran Papenberg; Elisabeth Winkler; Anna-Karin Welmer (BMC, 2020)
Abstract Objectives The beneficial effects of a physically active lifestyle in aging are well documented. Understanding the factors of importance for physical activity in older adults are therefore essential. Informed by animal and human data linking the dopamine system to motivation and reward processes, we investigated the associations between variations in dopamine genes and objectively measured physical activity and sedentary behaviour. Further, we aimed to verify whether higher age may exacerbate the impact of dopamine genes on physical activity. Methods We analyzed data from 504 older adults, 66-87 years, from the population-based Swedish National study on Aging and Care in Kungsholmen (SNAC-K). Physical activity was measured with activPAL accelerometers and DNA was extracted from blood samples for genotyping. We assessed the effects of three dopamine relevant genetic variations (DRD1, DRD2, and DRD3) on daily time in sedentary behavior, light-intensity physical activity and moderate-to-vigorous physical activity using analyses of covariance, adjusting for sex, age and physical function. Results Higher dopamine receptor efficacy was related to moderate-to-vigorous physical activity, but not to light-intensity physical activity or sedentary time. DRD1 explained 2.7% of variance in moderate-to-vigorous physical activity, with more pronounced effect in people aged ≥80 years, about 10% of explained variance. Conclusion Stronger genetic effects in older adults are in line with the well-established nonlinear effects of dopamine signaling on performance, expected to be exacerbated with aging. Individuals over 80 years, genetically predisposed to lower dopamine receptor efficacy, engaged on average 100 min/week in moderate-to-high physical activity, below the recommended levels beneficial for healthy aging. Our findings highlight that some individuals might need extra support to maintain a physically active lifestyle.